(untitled) (PANGEEA, 2025)
Concrete is one of the most consumed materials in the world. The use of conventional aggregates from exhaustible natural resources added to the mix is linked to a number of environmental impacts. The use of expanded polystyrene (EPS) in concrete recipes is an effective method because it allows the saving of conventional aggregates and allows the reuse of waste from constructions and demolitions. Although it is a relatively new material, lightweight concrete with expanded polystyrene has been the subject of study in various universities around the world as well as in the laboratories of various companies involved in the field of construction, mainly due to its low specific mass and good thermal insulation capacity.